2022
DOI: 10.1093/mnras/stac2546
|View full text |Cite
|
Sign up to set email alerts
|

MUSE–ALMA haloes VII: survey science goals & design, data processing and final catalogues

Abstract: The gas cycling in the circumgalactic regions of galaxies is known to be multi-phase. The MUSE-ALMA Haloes survey gathers a large multi-wavelength observational sample of absorption and emission data with the goal to significantly advance our understanding of the physical properties of such CGM gas. A key component of the MUSE-ALMA Haloes survey is the multi-facility observational campaign conducted with VLT/MUSE, ALMA and HST. MUSE-ALMA Haloes targets comprise 19 VLT/MUSE IFS quasar fields, including 32 zabs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 145 publications
0
3
0
Order By: Relevance
“…Ly𝛼 absorption studies of H i in the CGM of the Milky Way have shown evidence for a large amount of atomic gas at N(H i) ≥ 10 18 cm −2 (e.g., Richter et al 2017). The circumgalactic H i in external galaxies has been studied using Ly𝛼 absorption lines at 𝑧 ⪅ 0.2−0.85 (e.g., Borthakur et al 2016;Péroux et al 2022). These studies have revealed a strong correlation between the atomic gas mass fraction (M HI /M ★ ) and the impact-parameter-corrected equivalent width of Ly𝛼 absorbers, suggesting a physical connection between the atomic ISM and the CGM.…”
Section: Introductionmentioning
confidence: 99%
“…Ly𝛼 absorption studies of H i in the CGM of the Milky Way have shown evidence for a large amount of atomic gas at N(H i) ≥ 10 18 cm −2 (e.g., Richter et al 2017). The circumgalactic H i in external galaxies has been studied using Ly𝛼 absorption lines at 𝑧 ⪅ 0.2−0.85 (e.g., Borthakur et al 2016;Péroux et al 2022). These studies have revealed a strong correlation between the atomic gas mass fraction (M HI /M ★ ) and the impact-parameter-corrected equivalent width of Ly𝛼 absorbers, suggesting a physical connection between the atomic ISM and the CGM.…”
Section: Introductionmentioning
confidence: 99%
“…This enriched gas comprises the intergalactic medium (IGM) and circumgalactic medium (CGM), which consists of diffuse, multiphase gas that lies within the virial radii of galaxies (Tumlinson et al 2017). This tenuous reservoir plays a crucial role in regulating a galaxy's supply of gas, as stellar-driven feedback deposits enriched material beyond the disk that can recycle through the galaxy on a variety of timescales (Fielding et al 2017;Peroux & Howk 2020;Chadayammuri et al 2022;Pandya et al 2022;Péroux et al 2022). However, studying the connections between low-mass galaxies and the CGM at high redshift is challenging because the gas structures are intrinsically faint.…”
Section: Scientific Motivationmentioning
confidence: 99%
“…Significant progress has been made over the last few decades in statistically characterizing the distribution and physical conditions of the multiphase halo gas by cross-correlating absorption lines and galaxy surveys at ★ E-mail: rajeshwari.dutta@unimib.it 𝑧 < 2 (e.g. Prochaska et al 2011a;Tumlinson et al 2013;Chen et al 2020;Dutta et al 2020Dutta et al , 2021Wilde et al 2021;Berg et al 2022;Péroux et al 2022;Weng et al 2022), and at 𝑧 > 2 (e.g. Rudie et al 2012;Turner et al 2014;Bielby et al 2020;Lofthouse et al 2020Lofthouse et al , 2023Muzahid et al 2021).…”
Section: Introductionmentioning
confidence: 99%